Estudio de seropositividad de anticuerpos frente a neospora caninum en el ganado bovino de la zona de Tenjo – Cundinamarca (2022)
Neospora caninum is an obligate intracellular protozoan belonging to the phylum Apicomplexa responsible for the disease called Neosporosis, which causes important reproductive alterations in cattle, such as abortions between the third and ninth month of gestation, stillbirths, fetal mummification or abortions in an advanced stage of pregnancy. autolysis and embryonic resorption; It mainly affects dairy cattle and has been reported as an important cause of abortion in different parts of the world.